2010
DOI: 10.1021/nl9039795
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-Assisted Electroluminescence from Metallic Carbon Nanotubes and Graphene

Abstract: We report on light emission from biased metallic single-wall carbon nanotube (SWNT), multiwall carbon nanotube (MWNT) and few-layer graphene (FLG) devices. SWNT devices were assembled from tubes with different diameters in the range 0.7-1.5 nm. They emit light in the visible spectrum with peaks at 1.4 and 1.8 eV. Similar peaks are observed for MWNT and FLG devices. We propose that this light emission is due to phonon-assisted radiative decay from populated pi* band states at the M point to the Fermi level at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 36 publications
3
68
0
1
Order By: Relevance
“…This broadband non linear-PL arises from recombination of a distribution of non-equilibrium electrons and holes, generated by rapid scattering between photo-excited carriers after optical excitation 15 . It scales with the number of layers and can be used as a quantitative imaging tool, as well as to reveal the hot electron-hole plasma dynamics 15 , Fig 1c. Electroluminescence was also recently reported in pristine graphene 31 . Although the power conversion efficiency is lower than carbon nanotubes (CNTs), this could lead to novel emitting devices based entirely on graphene.…”
Section: Luminescencementioning
confidence: 58%
“…This broadband non linear-PL arises from recombination of a distribution of non-equilibrium electrons and holes, generated by rapid scattering between photo-excited carriers after optical excitation 15 . It scales with the number of layers and can be used as a quantitative imaging tool, as well as to reveal the hot electron-hole plasma dynamics 15 , Fig 1c. Electroluminescence was also recently reported in pristine graphene 31 . Although the power conversion efficiency is lower than carbon nanotubes (CNTs), this could lead to novel emitting devices based entirely on graphene.…”
Section: Luminescencementioning
confidence: 58%
“…17 The observation of visible electroluminescence from multilayer graphene systems has also been reported by several authors. 18 Biswas et al 19 have reported tunable electroluminescence from planar graphene/SiO 2 structures. Dong et al 20 have reported blue luminescence with a high quantum yield.…”
Section: Introductionmentioning
confidence: 99%
“…Only 2.3% of incident visible light is adsorbed by monolayer graphene, and the absorption of light linearly increases with the number of layers [76]. According to Loh et al [74], the most notable and unexpected consequence of the atomic structure of RGO is the observation of near-infrared, visible, and ultraviolet fluorescence [77], [78]. Furthermore, graphene can improve the performance of optical sensors because of its enhanced ability to adsorb biomolecules, and the higher density of states improves surface electromagnetic wave propagation.…”
Section: Optical Propertiesmentioning
confidence: 99%